Eficacia analgesica de morfina vs fentanilo asociado a bupivacaina 5% en anestesia subaracnoidea para el manejo del dolor postquirurgico en pacientes post cesareadas en el Hospital Bélen de Trujillo - Chafloque Guaylupo, Christian José (2019)
Introduction: The use of neuraxial anesthetic techniques has been related to a decrease in maternal mortality associated with anesthesia, considering the use of neuraxial opioids instead of intermittent parenteral boluses with or without rescues; the post-cesarean surgical pain interferes with the mother-child relationship, with negative consequences for this important binomial, so post-cesarean analgesia is of great importance. Objective: To compare the postoperative analgesic efficacy of Morphine vs Fentanyl associated with 5% bupivacaine in subarachnoid anesthesia in patients cesarean at the Bethlehem Hospital in Trujillo. Method: This study corresponds to an experimental, prospective, comparative, clinical efficacy trial. Conclusion: The use of Morphine associated with a local anesthetic is suitable for the management of post-surgical pain in patients undergoing cesarean section by subarachnoid anesthesia.